(untitled) (International Journal of Innovative Research in Engineering & Management, 2022)
The evident truth is that concrete is the most generally involved building material for a wide range of exercises in the development business overall and will keep going for a really long time. In the past few decades, fabrication of high performance concrete(HPC) has attracted the attention of many researchers worldwide. High performance concrete is that concrete in which the working of concrete is better to that of ordinary concrete in terms of durability and strength properties. This research article derived its motivation from the fact that fabrication of HPC with factory made derivatives not only ensures high strength and durability but also is eco-friendly in nature. As a result, the principle admixtures used in this research are: Silica Dust, Residual ash and Steel Slag Aggregate. A range of tests (tests of Resistance of acid, test for Resistance of salt, sulphate and tests of water absorption)have been performed to observe the properties of admixtures prepared. Results show that SFSSAC, RASSAC, SFRAC and SFRASSAC admixture outperforms the other CC blend and seems to be very promising in the near future.